How Does Creatine Supplementation Affect Physical Performance and Muscle Recovery? - A Literature Review of Its Effects, Mechanisms of Action, Safety and Side Effects - Pacanowska, Martyna; Blecharczyk, Małgorzata; Zydlewski, Igor; Mrozek, Martyna; Nowik, Alicja; Sękulski, Marcin; Kosiński, Maciej; Jakubiec, Paweł (Quality in Sport, 2025)
Introduction: Creatine is a naturally occurring compound that plays a primary role in energy metabolism, particularly within muscle cells. Its main sites of synthesis include the liver, kidneys, and pancreas [1,2]. This compound is crucial for muscle recovery following exercise. Creatine’s ability to rapidly replenish ATP stores reduces fatigue and muscle soreness, thereby accelerating the recovery process. By increasing the availability of phosphocreatine in muscle cells, creatine significantly enhances the capacity to perform both short-duration and high-intensity exercises [4,8]. This allows athletes to complete more repetitions per set and recover faster between sets. Consequently, creatine supplementation has gained increasing popularity, particularly among athletes and physically active individuals. Additionally, creatine’s influence on muscle protein synthesis is also linked to its ability to improve muscle cell hydration [15]. Aim of the Study: The aim of this study is to evaluate the impact of creatine supplementation on physical performance and muscle recovery, as well as to review its efficacy, safety, and potential side effects. Material and Methods: A review and analysis of randomized clinical trials and clinical studies from 2010 to 2025 available in PubMed and Google Scholar. Conclusions: Research findings indicate that long-term creatine use does not cause significant adverse side effects. Individuals supplementing with creatine have shown an increase in lean body mass without any undesirable effects on liver and kidney function. By improving muscle strength and endurance, creatine helps stabilize joints, thereby reducing the risk of musculoskeletal injuries [13]. From a practical perspective, these findings provide valuable insights for athletes, coaches, and physically active individuals striving to enhance both short-term and long-term training outcomes through creatine supplementation.